MISLA²: A System to Information Retrieval in Labour Lawsuits using Legal Ontologies and Regular Expressions - Rodrigues, Cleyton M. O.; Fernandes, Bruno J. T.; Silva, Leandro H. S.; Barrientos, David J.; Rocha, Allana L. S.; Sobral, Paulo Christiano; Souza, Bruno; Feitosa, Dionizio; Guimarães, Mabel; Barreto, Juliana (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2021: Anais do XVIII Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2021.18267, 2021)
Electronic Legal Proceedings are a worldwide legal phenomena, allowing the use of computerized systems for the creation and monitoring of procedural acts in the most diverse legal bodies. On one hand, it allows greater transparency in the conduct of procedural acts, on the other, it has contributed to the bottleneck of open but unresolved lawsuits each year. Nowadays, Information Retrieval to automate the processing of these procedural objects is at the forefront of computer systems for Law. In this study, we present MISLA 2 , a system to retrieve orders and preliminaries from judicial labour sentences through ontological models built from previous cases. Instead of tied and difficult-to-maintain domain specification models, we demonstrate how light ontologies, in conjunction with regular expressions for extracting significant portions of the text, can achieve the desired results. In addition, empirical experiments carried out with real labour lawsuits evidence that results are quite promising.